Solidarity Divided : The Crisis in Organized Labor and a New Path toward Social Justice - Fletcher, Bill, Jr (Book collections on Project MUSE., 2008)
The U.S. trade union movement finds itself today on a global battlefield filled with landmines and littered with the bodies of various social movements and struggles. Candid, incisive, and accessible, Solidarity Divided is a critical examination of labor's current crisis and a plan for a bold new way forward into the twenty-first century. Bill Fletcher and Fernando Gapasin, two longtime union insiders whose experiences as activists of color grant them a unique vantage on the problems now facing U.S. labor, offer a remarkable mix of vivid history and probing analysis. They chart changes in U.S.